Rancangan Aplikasi Marketplace Umkm Keripik Balado Salsabila Di Kota Padang Meggunakan Aplikasi Blogger - Oktavia, Nabilla; Chairunnisa, Fadilla Chairunnisa; Nadinda, Nadinda; Riesa, Rafidola Mareta Riesa; Sularno, Sularno (CV. ITTC INDONESIA, 2023)
– This foundational learning project's goal is to impart knowledge about innovative e-commerce applications in Balado Salsabila Chips in order to increase its effectiveness and efficiency. In order to build a market using the Blogger system, a qualitative research methodology was employed with data sources from one of the UMKM in Padang City, namely Balado Salsabila Chips. Surveys and interviews served as data collection methods. In accordance with research requirements, data collection tools include writing instruments like pens and telephones for recording significant events as well as for gathering documented proof. Salsabila's Balado Chips want to employ something novel, inventive, and creative, according to the research findings, in order to effectively manage risks and compete with new technology. Keywords : UMKM, Action-Oriented Thinking, Managing Risk, and Entrepreneurship